A framework for dependability evaluation of PROFIBUS networks - Carvalho, José Augusto (2003)
Fieldbus networks have been assuming a high acceptance in the industrial environment, replacing the old centralized control architectures. Due to time critical nature of the tasks involved in these environments, the fulfillment of dependability attributes is usually required. Therefore the dependability is an important parameter on system design, which should be evaluated. Several factors can affect system dependability. The environmental ones are the most common and due to the particularity of the industrial environment this susceptibility is increased. In this paper it is proposed a framework based on fault injection techniques, supported by a hardware platform which emulates a fault set, representative of industrial environment scenarios, intending to disturb data communications on a PROFIBUS network. From these fault injection experiments, relevant data is gathered and a further analysis is carried out to evaluate dependability attributes.